Study on Tensile Damage Constitutive Model for Multiscale Polypropylene Fiber Concrete - Ninghui Liang; Jifei Dai; Xinrong Liu (Advances in Materials Science and Engineering)
Polypropylene fibers perform well in roughness enhancement and corrosion resistance. They can dissipate energy when cracks occur in concrete. Furthermore, they can improve the concrete tensile properties by synergistic work with it. To study the tensile properties of the multiscale polypropylene concrete, uniaxial tensile strength of 18 fiber reinforced and 3 plain concrete specimens was experimentally tested using the paste steel method. The test results indicate that both the strength and the peak strain can be substantially improved. Based on the results, a tensile damage constitutive model was proposed and implemented into FLAC3D for numerical experimentation. The numerical results are consistent with the experimental observations in general and some discrepancies are discussed.